THE INFLUENCE OF WORK MOTIVATION BY THE HEAD OF SERVICE ON EMPLOYEE PERFORMANCE IN THE POPULATION CONTROL AND FAMILY PLANNING SERVICE (DPPKB) SUKABUMI - Irvi Deastiani Ripa'i; Tuah Nur; Dian Purwanti (Program Studi Doktor Ilmu Administrasi, FISIP, Universitas 17 Agustus 1945 Surabaya, 2023)
Work motivation by the Head of Service on Employee Performance in the Population Control and Family Planning Service (DPPKB) of Sukabumi Regency is significant. Based on the results of research and discussion conducted by researchers, it seems that there are still deficiencies in the presentation and writing of data. For future research, it is expected to look for other factors that influence employee performance and be able to analyze other, broader subjects. The area for taking respondents in this study was limited to certain locations, so that further research is expected to expand the area of research. So that it can obtain representative results from various other regions. Employees at the Population Control and Family Planning Service (DPPKB) of Sukabumi Regency are one of the most valuable assets of the Sukabumi Regency government, therefore it is necessary to pay attention to the development of human resource capabilities (HR) so that in carrying out their duties they have good performance, so that the services provided to the community can work better. The aims of this study are 1) To find out the work motivation techniques carried out by the Head of Service at the Population Control and Family Planning Service (DPPKB) of Sukabumi Regency; 2) To find out the performance of employees at the Population Control and Family Planning Service (DPPKB) of Sukabumi Regency; 3) To find out how much influence the motivation of the Head of Service has on the performance of employees of the Population Control and Family Planning Service (DPPKB) of Sukabumi Regency. In this study, researchers will use quantitative research methods with a descriptive approach. In this study using descriptive statistics. The population in this study were employees of the Population Control and Family Planning Office (DPPKB) of Sukabumi Regency.